Persepsi Pengunjung dalam Penilaian Infrastruktur Pariwisata Pesisir Pantai Indah Kapu: Fokus pada Ketersediaan Fasilitas Pengunjung - Rustan, Fathur Rahman; Puspaningtyas, Retno; Ardiansyah, Muh.; Anggraini, Yuyun (Universitas Sulawesi Tenggara, 2024)
Tourism facilities are the completeness of tourist destinations that can meet the needs of tourists in enjoying their tour. Tourism facilities are completeness that must exist in tourist destinations that can serve tourists to enjoy tourist visits. Tourism facilities are also considered as physical elements designed and established to serve visitors. Tourism facilities are divided into three, namely basic, complementary, and supporting tourism facilities. Complementary facilities are facilities with the aim that tourists can be comfortable and stay longer. Forms of complementary facilities include sports facilities, secondary tourism facilities, and other entertainment. The availability of tourism facilities at Pantai Indah Kapu, Sani - Sani village, Samaturu sub-district, Kolaka district, is categorised as moderate. This shows that the value of the public perception of the availability of facilities. The level of visitor satisfaction with Pantai Indah Kapu tourist attraction, categorised as moderate, this affects the public perception of tourist satisfaction.